Maskulinitas dan Hubungan Interpersonal Perspektif Al-Qur’an - Lestari, Rosa (REVELATIA Jurnal Ilmu al-Qur`an dan Tafsir, 2025)
During this discussion, gender is only been about women because in the past (before the 19th century) women were not respected. So that the existence of men and their roles in the present (21st century AD) have received less attention to be studied as a special education, even though it is clear in the Qur'an, Surah An-Nisa verse 34, that "men are leaders for women" as Yusuf Ali translated qawwamah: men are protectors and maintainers for women. In order to realize the men reflected in the verse of QS. An-Nisa '[4]: 34, an in-depth study is needed on the biological and emotional side of men or what is commonly called masculinity. The concept of masculinity is not static and can change. Masculinity is closely related to interpersonal relationships, namely interactions with women, children and other men. This article aims to present a discourse analysis of how language and discourse shape the construction of masculinity from an Islamic perspective.